Thoughts of Rabindranath Tagore on Education in his writings - Chattopadhyay, Dr. Arunava (IJRDO - Journal of Social Science and Humanities Research, 2017)
Rabindranath was the worshipper of beauty. He searched for the beauty throughout his life. For this reason his writings have become significant. Philosophical idea of education of Rabindranath Tagore was influenced by his personal lifestyle. He was impressed by the ancient Indian system and there is a clear reflection of that system in his literature. Self education builds up self- realization. It is assimilated in education. So a student must have self confidence. Purpose of education is to introduce one with the whole universe. So the syllabus of education is the main bearer of that culture. He advised to take special care on making syllabus. So that the human culture is reflected on it. Philosophical idea of Education focus on his Poems, Short Stories, Novels, Dramas and also in Articles.